Evaluasi Aplikasi Bio Urin Sapi dan Cendawan Mikoriza terhadap Karakter Morfo-fisiologi Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Sylvia Madusari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Organic fertilizer in the form of fermented cow urine has a high nutrient content and the presence of mycorrhizal fungi can increase root capacity in the absorption of nutrients needed for plant growth. The purpose of this study was to analyze the role of a combination of cow bio-urine application and mycorrhizal fungi at different doses on the morphology and physiology of oil palm plants in the initial breeding. This research was conducted for 6 months by using a two-factor Complete Randomized Design (CRD). The first factor is the application of three doses of mycorrhizal fungi, namely: CMA0 (red yellow subsoil podsolic 100%), CMA1 (10 g mycorrhizal fungus), CMA2 (20 g of mycorrhizal fungi); and the second factor is the application of three doses of cow biourine, namely: BU00 (red yellow podsolic subsoil 100%), BU01 (20% cow urine), BU02 (30% cow urine). The results showed that there was a real interaction between the administration of mycorrhizal fungi and bio urine of cow on the stem diameter of 3 BST and 4 BST. At the end of the observation (4 BST), the response of oil palm seedlings to the parameters of seedling height, number of leaves, stem diameter, leaf area, leaf greenness, seedling biomass, seed root canopy ratio, showed a tendency of higher values ​​in the application of 10 gram mycorrhizal fungi. cow urine 20% compared to other treatments and controls.